Spatial-temporal dynamics of red tide precursor organisms at the Pacific coast of North and Central America - Sierra-Beltrán, A P; Lluch-Cota, D B; Lluch-Cota, S E; Cortés-Altamirano, R; Cortés-Lara, M C; Castillo-Chávez, M; Carrillo, L; Pacas, L; Víquez, R; García-Hansen, I (Revista de biología tropical, 2004)
The Pacific coast of Central and North America has long been and still is impacted by the flourishing of microalgal populations known as Harmful Algal Blooms (HABs). The organisms that have caused recent HABs episodes in the region are among others, Gymnodinium catenatum, Pyrodinium bahamense var. compressum, and recently Cochlodinium cf. catenatum. In spite of the accumulated effects on the human health, the economic activities and the environment, scarce information is available on the subject. The augmented use of coastal zones for human activities is also paralleled by increased awareness of global climate changes. Thus, it is not an easy task to discriminate anthropogenic or natural phenomena, or both, as the major driving forces. The long-term data sets available for limited regions, as well as some sporadic observations during notorious blooms, allowed us to discriminate major changes in the biodiversity and biogeography of HAB organisms. Main changes refer to number of events, covered area, duration and frequency, number of blooming species and appearance of not previously reported harmful taxa. The variables more clearly related to these dynamic phenomena, seems to be sea surface temperature and wind force, but it is not yet possible to weight their contributions. The participation of rain is not fully evaluated to date. The collaborative communication among small-budget monitoring operations in the region allowed to "pass the voice" about peaking concentrations of HAB organisms, diminishing the risk of poisoning.